Experimental Investigation on the Self-Healing Efficiency of Araldite 2011 Adhesive Reinforced with Thermoplastic Microparticles - Ozer, Halil; Erbayrak, Engin (INTECH EUROPE, 2016)
Newly developed self-healing technologies allow self-repair of adhesively bonded joints without the need for replacing the damaged joint with a new one. This study addresses to define experimentally the self-healing ability and efficiency of the Araldite 2011 epoxy adhesive reinforced with the thermoplastic co-polyester (TPC). Heating the joint results in melting the co-polyester in adhesive, and then it is expected to repair the damaged region by the melted co-polyester. Firstly, before applying the self-healing process, a preliminary study was applied to define whether selected adhesive is compatible with the thermoplastic particles in terms of self-healing. From the initial results, it is seen that Araldite 2011 adhesive is suitable for use in the self-healing mechanism. In the healing cycle, initial crack in the reinforced adhesive was propagated until 30 mm during the double cantilever beam (DCB) testing. The fractured specimens were repeatedly healed in terms of the close-then-heal (CTH) scheme until no healing has taken place. After the healing process was completed, the healing efficiency was defined using the fracture energy values. In this study, the healing process was repeated two times with the acceptable healing efficiencies. It is concluded that the damaged reinforced adhesive can repair itself with a considerable healing efficiency.
Keywords: Self-healing; Araldite 2011; Thermoplastic additive; Healing efficiency; DCB test; STRENGTH; COMPOSITES; JOINTS; EPOXY; Materials Science